Global Value Chains and the Exchange Rate Elasticity of Exports - Hannan, Swarnali (IMF Working Papers; Working Paper, 2015)
This paper analyzes how the formation of Global Value Chains (GVCs) has affected the exchange rate elasticity of exports. Using a panel framework covering 46 countries over the period 1996-2012, we first find some suggestive evidence that the elasticity of real manufacturing exports to the Real Effective Exchange Rate (REER) has decreased over time. We then examine whether the formation of supply chains has affected this elasticity using different measures of GVC integration. Intuitively, as countries are more integrated in global production processes, a currency depreciation only improves competitiveness of a fraction of the value of final good exports. In line with this intuition, we find evidence that GVC participation reduces the REER elasticity of manufacturing exports by 22 percent, on average.